The exercise pressor reflex and active O2 transport in peripheral arterial disease. Issue 20 (22nd October 2019) - Stavres, Jon; Sica, Christopher T.; Blaha, Cheryl; Herr, Michael; Wang, Jianli; Pai, Samuel; Cauffman, Aimee; Vesek, Jeffrey; Yang, Qing X.; Sinoway, Lawrence I.
Abstract: It is unclear if the exaggerated exercise pressor reflex observed in peripheral arterial disease (PAD) patients facilitates Oxygen (O2 ) transport during presymptomatic exercise. Accordingly, this study compared O2 transport between PAD patients and healthy controls during graded presymptomatic work. Seven PAD patients and seven healthy controls performed dynamic plantar flexion in the bore of a 3T MRI scanner. Perfusion, T2 * (an index of relative tissue oxygenation), and SvO2 (a measure of venous oxygen saturation) were collected from the medial gastrocnemius (MG) during the final 10 seconds of each stage. Blood pressure was also collected during the final minute of each stage. As expected, the pressor response to presymptomatic work (4 kg) was exaggerated in PAD patients compared to controls (+14 mmHg ± 4 and +7 mmHg ± 2, P  ≤ 0.034). When normalized to changes in free water content (S0 ), T2 * was lower at 2 kg in PAD patients compared to controls (−0.91 Δms/ΔAU ± 0.3 and 0.57 Δms/ΔAU ± 0.3, P  ≤ 0.008); followed by a greater increase in perfusion at 4 kg in the PAD group (+18.8 mL/min/100g ± 6.2 vs. −0.21 mL/min/100g ± 3.2 in PAD and controls, P ≤  0.026). Lastly, SvO2 decreased at 4 kg in both groups (−13% ± 4 and −2% ± 4 in PAD and controls, P  ≤ 0.049), suggesting an increase in O2 extraction in the PAD group. Based on these findings, O2 transport appears to be augmented during graded presymptomatic work in PAD patients, and this may be partially mediated by an exaggerated pressor response. Abstract : MRI was used to compare oxygen (O2) transport between peripheral arterial disease (PAD) patients and healthy controls during graded presymptomatic exercise. Blood pressure (BP) and muscle perfusion both increased more in PAD patients compared to controls, while venous O2 saturation concurrently decreased. O2 extraction also correlated well with BP in our subjects, suggesting that the rise in BP in PAD contributed to the enhanced perfusion at the second workload.